Keputusan Konsumen Terhadap Pembelian Selada (Lactuca sativa L.) di Pasar Modern Kota Makassar - Amelia S., Putri; Amrullah, A. (Jurnal Sosial Ekonomi Pertanian, 2025)
Lettuce (Lactuca sativa L.) is one of the popular leaf vegetables with high nutritional value. Lettuce consumption increases along with the healthy lifestyle trend that encourages people to choose nutritious, fresh, and natural foods. This study aims to analyze the factors that influence consumer decisions in purchasing lettuce in modern markets in Makassar City. The study was conducted in several modern markets with 96 respondents who were consumers of lettuce buyers. Data were collected using a questionnaire and analyzed using multiple linear regression methods to determine the effect of independent variables on the dependent variable. The results of the analysis showed that of the 13 variables studied, there were seven variables that had a significant positive effect on consumer decision to purchase lettuce, namely product quality, freshness, income, knowledge, taste, product packaging, and lifestyle. Meanwhile, the price variable had a significant negative effect on purchasing decisions. Other variables such as product availability, location, promotion, and social and cultural factors did not show a significant effect. These findings indicate that consumer preferences in purchasing lettuce are more determined by quality, product image, and internal consumer factors than external aspects such as promotion or sales location.